Evaluation of Symptoms in Cases of Otitis Media - A Clinical Study - Prasun Kumar Chattopadhyay (Asian Journal of Medical Research, 2019)
Background: Otitis media (OM) is a group of inflammatory diseases of the middle ear. The present study was conducted to assess the cases of Otitis media. Subjects and Methods: The present study was conducted on 112 patients of OM of both genders. The case history and general physical examination was performed. General symptoms and types of OM were evaluated. Results: Out of 112 patients, males were 52 and females were 60. Acute OM was seen in 30 males and 32 females and chronic OM was seen in 22 males and 28 females. Common symptoms were cold seen in 68, retro-auricular pain in 17, fever in 80, hearing impairment in 52, ear discharge in 72, tinnitus in 8, vertigo in 45 and facial asymmetry in 26. Conclusion: Authors suggested that Otitis media is a common ear problem. They observed higher female prevalence than males.